Site-specific nutrient management is a key for enhancing productivity of rapeseed-mustard in India (Journal of Oilseed Brassica, 2026)
In India, rapeseed-mustard alone contributes in total oil production to the extent of about 24% with its average productivity of about 1.00 t ha-1. Analysis of 1601 soil samples from major mustard growing areas representing 14 agro-ecological sub-regions (AESRs) indicated widespread multi-nutrient deficiency involving 2 to 6 nutrients including NK, NKS, NKB, NPKS, NKSZn and NPKSZnB. Incidence and expansion of such multi-nutrient deficiencies in Indian soils owing to inadequate and unbalanced nutrient input through fertilizers is considered one of the major constraints in enhancing productivity of oilseed crops. In this context, different nutrient supply options namely T1: SSNM; T2: State ad-hoc recommendation plus potassium (SR) + K; T3: SR; T4: Farmer’s fertilizer practice (FFP) + K; and T5: FFP were evaluated in Lohtaki village district Gurgaon representing AESR 4.1 with pearlmilet-mustard cropping system. On an average, mustard grain yield responses over FFP across the experiments were the highest in SSNM (85%), followed by SR+K (40%) and SR (24%). Average net return over FFP in pearlmillet-mustard cropping system was higher (Rs. 43963 ha-1) under SSNM, followed by SR+K (Rs. 26092 ha-1) and SR (Rs. 15693 ha-1). In all these experiments, SSNM proved superior to state recommendation and farmers’ fertilizer practice in terms of annual crop yields, nutrient recovery, soil fertility restoration and net economic returns. Site-specific nutrient management (SSNM) seems to be one of effective ways to improve nutrient supplying capacity of soil and enhance the productivity of mustard, which in turn will help in achieving much needed self sufficiency in oilseeds production in India.